Doctor of Pharmacy internship module in pediatrics at a Teaching Hospital in Lalitpur, Nepal- A preliminary report - Dhakal, Ajya Kumar; Ravi Shankar, P; Shrestha, Devendra (Journal of Kathmandu Medical College, 2014)
Doctor of Pharmacy is a relatively new academic course in Nepal. The course is divided into two phases. The first phase includes first and second academic year with two semesters in each year and second phase has mandatory hospital internship in different clinical departments for 12 month during third year. Doctor of pharmacy is the highest degree offered in clinical and hospital pharmacy and aims to produce professionals well versed in pharmacotherapy. We developed an internship training module for these students in paediatrics and believe that such module will help in production of trained pharmacy manpower and assist other clinical departments to develop internship training modules for doctor of pharmacy students. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10924 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 41-45